A novel microstructural reconstruction phenomenon and electrochemical performance of cactus-like SnO2/carbon composites as anode materials for Na-ion batteries. (10th August 2017) - Lu, Xiaoxiao; Wu, Guolong; Xiong, Qinqin; Qin, Haiying; Ji, Zhenguo; Pan, Hongge
Highlights: Cactus-like SnO2 /carbon was prepared by two step hydrothermal synthesis. A structural reconstruction phenomenon was observed after battery cycling. The sample is demonstrated with an enhanced cyclability as anode for Na battery. The carbon component is proven to introduce a high quality SEI. Abstract: A hydrothermal synthesis and a subsequent carbon coating process have been used to prepare a cactus-like SnO2 /carbon composite as anodes for Na-ion batteries. This composite was demonstrated with enhanced cyclability and outstanding electrochemical performance when used as anode for Na-ion batteries. It delivered an initial discharge capacity of 1259 mAh g −1, and then retained a high reversible capacity of around 500 mAh g −1 after 50 cycles at a current density of 20 mA g −1 . When the current density increased to 1200 mA g −1, a reversible capacity of 120 mAh g −1 can be obtained. Comparing the difference of microstructures before and after cycling, it is found that the cactus-like SnO2 /carbon composite presents a novel carbon coating introduced microstructural reconstruction phenomenon. Moreover, the carbon coating was proven to stabilize a spatial cactus structure and induce a high quality solid electrolyte interface (SEI) layer, which effectively enhanced the cyclablity of the cactus-like SnO2 /carbon composite. It is believed that carbon coating is an effective way to improve the electrochemical performance of the cactus-like SnO2 .